2021
DOI: 10.1002/hbm.25626
|View full text |Cite
|
Sign up to set email alerts
|

Identifying individuals with Alzheimer's disease‐like brains based on structural imaging in the Human Connectome Project Aging cohort

Abstract: Given the difficulty in factoring out typical age effects from subtle Alzheimer's disease (AD) effects on brain structure, identification of very early, as well as younger preclinical "at-risk" individuals has unique challenges. We examined whether agecorrection procedures could be used to better identify individuals at very early potential risk from adults who did not have any existing cognitive diagnosis. First, we obtained cross-sectional age effects for each structural feature using data from a selected po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This work demonstrates the possibility to use this technique, which requires only a single T1-weighted MRI, in diagnostic support clinically, as well as to screen individuals who are likely to be a candidate for more intensive biomarker assessment. Future work will apply the MSSM procedures in individuals with earlier impairment and/or pathology stages, MCI with conversion to other types of dementia, and preclinical at-risk individuals ( Li et al, 2021 ) to determine the benefits of these novel features.…”
Section: Discussionmentioning
confidence: 99%
“…This work demonstrates the possibility to use this technique, which requires only a single T1-weighted MRI, in diagnostic support clinically, as well as to screen individuals who are likely to be a candidate for more intensive biomarker assessment. Future work will apply the MSSM procedures in individuals with earlier impairment and/or pathology stages, MCI with conversion to other types of dementia, and preclinical at-risk individuals ( Li et al, 2021 ) to determine the benefits of these novel features.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that age-related changes may have a greater impact on imagebased diagnosis in patients outside the common onset ages because changes associated with later-life disease are subtle at very young patients, and age-related brain decline is severe in very old patients, which is leading to overestimation of those disease-free areas (Dukart et al 2011). Hence, age correction methods have been proposed for both MRI (Dukart et al 2011;Li et al 2021) and [ 18 F]FDG-based (Jiang et al 2018) diagnosis of dementia. The onset age for parkinsonism is generally around 55-65 years old, and some early onset cases may show symptoms in the early 20s, while some patients show symptoms at very old ages (i.e., late 80s).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a previous study including both diseases, we showed that distinct brain atrophy patterns could potentially help in differentiating AD and FTD (Falgàs et al, 2020 ). More recently, measures derived from MRI have been used within ML algorithms to differentiate these diseases (Bron et al, 2017 ; Li et al, 2021 ; Möller et al, 2016 ; Penny et al, 2007 ). These approaches have shown good results.…”
Section: Introductionmentioning
confidence: 99%